MORINGA OLEIFERA SEED OIL EXTRACTION BY MECHANICAL PRESSING - Grace Hutagaol, Rika
Found in animals and plants, fats and oils are one of the essential components offood. People these days have shift the use of animal fats to vegetable oils for a healthier lifestyle due to their high unsaturated fat content. One potential source of vegetable oil in Indonesia is moringa seeds. This study aims to determine the effect of seed moisture content and pressing temperature on the yield of moringa seed oil and to determine the characteristics of the oil. The tested oil characteristics include density, color, acid value, saponification value, and FTIR analysis. The experimental variations conducted in this study are the seed moisture content, in 10, 12, 16, and 18%, and the pressing temperature, in 90, 100, and 120°C. The obtained oil yield ranges from 16.69 to 22.93% w/w of moringa seeds, while the moringa oil recovery ranges from 47.78 to 64.61% w/w of moringa seed oil. The best yield and recovery were obtained with a variation of 10, 12, and 16% seed moisture content at a pressing temperature of 100°C. The density of the obtained oil ranges from 0.82 to 0.85 g/mL. The color of moringa seed oil tends to be different compared to commercial oil. The acid value and saponification value of moringa seed oil were found to be 1.82-2.52 mg KOH/gram of oil and 149.8-155.4 mg KOH/gram of oil, respectively. Furthermore, FTIR analysis results showed no significant difference in the functional groups present in each sample variation of the oil. For the selected best variation, based on the yield and recovery, which is the oil with 10, 12, and 16% seed moisture content at a pressing temperature of 100°C, an iodine value test was conducted, indicating that the iodine value is not significantly affected by the seed moisture content. It was also found that higher moisture content can decrease the antioxidant activity of the oil. Additionally, analysis of the moringa press cake showed that it still contains high levels of protein and contains the active compound 4-alpha-4 rhamnosyloxy-benzyl-isothiocyanate. With the presence of this active compound, the press cake can be utilized as a natural coagulant in wastewater treatment.